2018
DOI: 10.1080/0284186x.2018.1461926
|View full text |Cite
|
Sign up to set email alerts
|

Development of a normal tissue complication probability model for late unfavourable aesthetic outcome after breast-conserving therapy

Abstract: An NTCP model for late unfavourable AO after breast-conserving therapy was developed including seroma, axillary lymphadenectomy and V55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The model performed well with an Area Under the Curve (AUC) of the receiver operating curve 0.76 and bootstrap resampling resulting in AUC 0.75. The Hosmer-Lemeshow test assessing calibration was not significant, indicating good agreement between expected and observed unfavourable AO rates [11].…”
Section: Ntcp Modelmentioning
confidence: 87%
See 3 more Smart Citations
“…The model performed well with an Area Under the Curve (AUC) of the receiver operating curve 0.76 and bootstrap resampling resulting in AUC 0.75. The Hosmer-Lemeshow test assessing calibration was not significant, indicating good agreement between expected and observed unfavourable AO rates [11].…”
Section: Ntcp Modelmentioning
confidence: 87%
“…Currently, aesthetic outcome (AO) is becoming increasingly important because it influences the quality of life and psychosocial recovery after breast cancer treatment. An NTCP model to predict for the risk of long-term AO has previously been developed by our research group [11]. The nomogram included three variables: seroma, ALND and V55.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative risk (RR) ratios comparison according to normal tissue complication probability analysis for severe acute skin toxicity for intensity modulated proton plan without (IMPT 1 ) and with skin included in the cost function (IMPT 2 Severe acute skin reactions may be prodromal of consequential skin late effects [36] and prevention of these acute reactions may also avoid late effects which can impact on esthetic outcome and quality of life. Recently Kindts et al [37] developed a prediction model for late unfavorable esthetic outcome for breast-conserving therapy taking into account clinicopathological and dosimetric variables. The authors identified seroma, axillary lymphadenectomy, and breast volume receiving more than 55 Gy as predictive factors.…”
Section: Discussionmentioning
confidence: 99%